Case Report Euglycemic Ketoacidosis in patient with acute gastroenteritis with known case of Diabetes Mellitus diagnosed to be Latent Autoimmune Diabetes of Adulthood (LADA): Ketoacidosis in Latent Autoimmune Diabetes of Adulthood Rathod (Bombay Hospital Journal, 2024)
63-years female who is a known case of diabetes mellitus presented with history of vomiting and loose stool since 1 day following recent history of travel and outside food consumption. Patients blood sugar levels was within normal range.  Patient was hemodynamically stable. Patient started developing breathlessness in the ward and was shifted to the ICU and was tested for serum acetone urine ketone which tested positive and was started on IV insulin infusion and patient showed improvement, patient was diagnosed with Latent Autoimmune Diabetes of Adulthood in view of Euglycemic ketoacidosis.
Keywords: Diabetes Ketoacidosis; Latent Autoimmune Diabetes of Adulthood (LADA); Insulin level, C- peptide levels.